Therapeutic Effect of Curcumin on Hepatic iNOS Expression in a Rat (Rattus norvegicus) Preeclampsia Model - Desy Aulina Sururi; Mutiara Putri Nanda Rizki; Bambang Rahardjo; Novida Ariani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Preeclampsia is a pregnancy-specific disorder characterized by hypertension after 20 weeks of gestation and multisystem involvement, including hepatic dysfunction. Amplified oxidative stress and systemic inflammation contribute to liver damage, partly through the stimulation of inducible nitric oxide synthase (iNOS). Curcumin, a polyphenol derived from Curcuma longa, possesses strong antioxidant and anti-inflammatory properties and has been reported to inhibit iNOS expression in various disease models. The objective of this study was to evaluate the effect of curcumin on hepatic iNOS protein expression in a rat model of preeclampsia. A true experimental post-test-only control group design was employed. Twenty-five pregnant Wistar rats were randomly assigned to five groups: negative control, positive control (L-NAME-induced preeclampsia), and three treatment groups receiving curcumin at 30, 50, or 100 mg/kg body weight alongside L-NAME. Preeclampsia was induced by intraperitoneal administration of L-NAME (125 mg/kg body weight) from gestational day 13 to 19, during which curcumin was administered orally. Liver tissues were collected and subjected to immunohistochemical analysis to quantify iNOS expression. One-way ANOVA with post hoc testing (p < 0.05) revealed significant differences among groups. Quantitative ImageJ analysis iNOS expression (% positive area) showed: 5.06 (negative control), 77.00 (positive control), 64.34 (P1), 33.67 (P2), and 19.78 (P3), indicating a dose-dependent reduction in iNOS expression. Curcumin at 100 mg/kg body weight produced the most pronounced decrease in hepatic iNOS expression in preeclampsia-induced rats. These findings demonstrate that curcumin exerts hepatoprotective effects through the downregulation of iNOS in preeclamptic liver tissue and suggest its potential as an adjunctive therapeutic or preventive strategy for mitigating hepatic inflammation in preeclampsia. Further investigation in advanced preclinical and clinical studies is warranted. Keywords: Curcumin, iNOS, Oxidative stress, Hepatic Inflammation, Preeclampsia.